Capitalization and Social Transformation in the Grand Mall Maros, Indonesia - Adi Sumandiyar (International Journal of Qualitative Research, 2022)
This article aims to get in-depth information regarding the condition of capitalization and social formation in the Grand Mall Maros. This research uses a descriptive qualitative approach to exploring information about the involvement of all stakeholders in the development and construction of Grand Mall Maros. The results showed that building the basic structure of social cohesion to prevent social conflicts is a source of unequal control of urban space. This social reality must still be followed by an improvement in the quality of social life, especially for local communities, which ideally becomes a subordination of social formations in urban space.